The Effect of Leadership Style, Work, Culture and Motivation on Performance of The State Civil Apparatus on The Secretariat of The Regional People's Representative Board, Bekasi City, West Java - Jon Edy; Darlius Darlius; Mefida Ilyas (Universitas Muhammadiyah Jakarta, 2022)
This research wants to reveal whether there is an influence of leadership style, work culture and motivation on the performance of the state civil apparatus in the secretariat of the Regional Representative Council of Bekasi City, The performance of an organization is the achievement of the achievement of both quantity and quality results by deploying resources in a certain time. Using the help of SPSS V. 24 analysis in this study using Path Analysis which aims to find out the direct influence of variable Independent (X) on variable dependent (Y) and indirect influence (through variable interverning) on variable independent (Y), this study involved 117 respondents consisting of civil servants and some of them are honorees, Data collection techniques are carried out by spreading a list of questions or statements to all 117 respondents where the list of crawlers or statements has been conducted validity tests and reliability tests before, then the results of the respondent's answers are tabulated into Microsoft excel to facilitate in analyzing it, From the results of the analysis of the data in this study it can be concluded that leadership style, work culture and motivation either directly or indirectly (through interverning variables) and bai alone (partial) and simultaneously (simultaneously) show a significant influence on the performance of the state civil apparatus in the secretariat of the Regional People's Representative Council of Bekasi city.